-6x-4=-3x-22

Simple and best practice solution for -6x-4=-3x-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-4=-3x-22 equation:


Simplifying
-6x + -4 = -3x + -22

Reorder the terms:
-4 + -6x = -3x + -22

Reorder the terms:
-4 + -6x = -22 + -3x

Solving
-4 + -6x = -22 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-4 + -6x + 3x = -22 + -3x + 3x

Combine like terms: -6x + 3x = -3x
-4 + -3x = -22 + -3x + 3x

Combine like terms: -3x + 3x = 0
-4 + -3x = -22 + 0
-4 + -3x = -22

Add '4' to each side of the equation.
-4 + 4 + -3x = -22 + 4

Combine like terms: -4 + 4 = 0
0 + -3x = -22 + 4
-3x = -22 + 4

Combine like terms: -22 + 4 = -18
-3x = -18

Divide each side by '-3'.
x = 6

Simplifying
x = 6

See similar equations:

| 354=206+p | | 21.35-27.06x=34.19(19.22-37.81x) | | 11x-(9x-8)=12 | | a(a-4)=4a-(2a+4) | | 3x+6y=375 | | 20x^2y^2-4xy=0 | | 7x-3=-19-x | | 2/3x-4=11/4 | | 6x+1=-13+x | | 5u-8/4+4u-1/5=6 | | 15x+75=720 | | -m^2+14+(-6m^2+13+m^2)=0 | | 6x+9=-21+3x | | -42=2n+2+n | | (5/12)=((x+1)/4) | | 4x+5=5+5x | | 3+3t=17 | | 100=-2x | | 5w^2/10z^6 | | 7x-10-3x=6x-9 | | -2x+5-4(5-2x)+3x-(9-5x)+4= | | 5/2y-2/3=-5/4y-7 | | 2x+6(x+6)=68 | | 14v+6=2(5+7w)-4 | | 8x-3=2+7x | | 1-2x=3x-54 | | 21-7(19-x^2+6)-3x^2+1=0 | | -5/3v+4/3=-4v-4/5 | | 4x=3(4)-7 | | 1/3x12+7 | | 6x+8x-36=3+5x | | z+1.7=-18.1 |

Equations solver categories